New planar light source for the induction and monitoring of photodynamic processes in vitro - Bajgar, R; Pola, M; Hosik, J; Turjanica, P; Cengery, J; Kolarova, H (Journal of biological physics, 2020)
We recently developed a new light source that allows for the continuous monitoring of light-induced changes using common spectrophotometric devices adapted for microplate analyses. This source was designed primarily to induce photodynamic processes in cell models. Modern light components, such as LED chips, were used to improve the irradiance homogeneity. In addition, this source forms a small hermetic chamber and thus allows for the regulation of the surrounding atmosphere, which plays a significant role in these light-dependent reactions. The efficacy of the new light source was proven via kinetic measurements of reactive oxygen species generated during the photodynamic reaction of chloroaluminium phthalocyanine disulfonate (ClAlPcS2) in three cell lines: human melanoma cells (G361), human breast adenocarcinoma cells (MCF7), and human fibroblasts (BJ).
Keywords: nádorové buněčné linie; Reactive Oxygen Species; Models, Biological; Microplate reader; fibroblasty; lidé; biologické modely; Hot Temperature; Photodynamic effect; reaktivní formy kyslíku; světlo; vysoká teplota; Humans; Light; In vitro; Cell Line, Tumor; Light source; Fibroblasts